2020
DOI: 10.3847/1538-4357/abc41a
|View full text |Cite
|
Sign up to set email alerts
|

GRB Fermi-LAT Afterglows: Explaining Flares, Breaks, and Energetic Photons

Abstract: The Fermi-LAT collaboration presented the second gamma-ray burst (GRB) catalog covering its first 10 years of operations. A significant fraction of afterglow-phase light curves in this catalog cannot be explained by the closure relations of the standard synchrotron forward-shock model, suggesting that there could be an important contribution from another process. In view of the above, we derive the synchrotron self-Compton (SSC) light curves from the reverse shock in the thick-and thin-shell regime for a unifo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 91 publications
(144 reference statements)
0
17
0
Order By: Relevance
“…One satellite that has been foremost in studying GRBs is the Neil Gehrels Swift Observatory (Gehrels et al 2004) that has discovered many GRBs from low to high redshifts, with almost of all of them possessing an afterglow emission. The afterglow is a long-lasting (from minutes, hours, days, to even months and years) emission observed in several wavelengths from gamma-ray to radio (see, e.g., Sari & Piran 1999b;Kumar & Piran 2000;Panaitescu et al 2001;Soderberg et al 2006;Izzo et al 2013;Stratta et al 2013;Fraija 2015;Fraija et al 2020b). It most probably comes from an external forward shock (ES), where the GRB ejecta that move at relativistic speeds, made up of electrons and positrons (e − , e + ) and heavier nuclei, interact with the interstellar medium (Paczynski & Rhoads 1993;Meszaros & Rees 1994, 1997Sari & Piran 1995).…”
Section: Introductionmentioning
confidence: 99%
“…One satellite that has been foremost in studying GRBs is the Neil Gehrels Swift Observatory (Gehrels et al 2004) that has discovered many GRBs from low to high redshifts, with almost of all of them possessing an afterglow emission. The afterglow is a long-lasting (from minutes, hours, days, to even months and years) emission observed in several wavelengths from gamma-ray to radio (see, e.g., Sari & Piran 1999b;Kumar & Piran 2000;Panaitescu et al 2001;Soderberg et al 2006;Izzo et al 2013;Stratta et al 2013;Fraija 2015;Fraija et al 2020b). It most probably comes from an external forward shock (ES), where the GRB ejecta that move at relativistic speeds, made up of electrons and positrons (e − , e + ) and heavier nuclei, interact with the interstellar medium (Paczynski & Rhoads 1993;Meszaros & Rees 1994, 1997Sari & Piran 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This high-energy emission shows two very interesting features: photons with energy >100 MeV peak later (Omodei 2009;Ackermann et al 2013;Ito et al 2013Ito et al , 2014Warren 2018;Ajello et al 2019) and last longer than the sub-MeV photons detected by the GBM. Indeed, the study of three GRBs at energy >100 MeV (080916C, 090510, 090902B) has led to the interpretation that LAT photons are associated with the afterglow rather than the prompt emission and are generated via synchrotron emission in the ES (Mészáros & Rees 1993Waxman 1997aWaxman , 1997bAbdo et al 2009aAbdo et al , 2009bOmodei 2009;De Pasquale et al 2010;Kumar & Barniol Duran 2010;Razzaque 2010;Kouveliotou et al 2013;Wang et al 2013;Beniamini et al 2015;Fraija et al 2020). In particular, the works of Kouveliotou et al (2013), Wang et al (2013), Beniamini et al (2015), and Fraija et al (2020) have shown that GRBs detected by LAT can be self-consistently modeled using radio, optical, X-ray, and sub-GeV LAT observations self-consistently within the ES model.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the study of three GRBs at energy >100 MeV (080916C, 090510, 090902B) has led to the interpretation that LAT photons are associated with the afterglow rather than the prompt emission and are generated via synchrotron emission in the ES (Mészáros & Rees 1993Waxman 1997aWaxman , 1997bAbdo et al 2009aAbdo et al , 2009bOmodei 2009;De Pasquale et al 2010;Kumar & Barniol Duran 2010;Razzaque 2010;Kouveliotou et al 2013;Wang et al 2013;Beniamini et al 2015;Fraija et al 2020). In particular, the works of Kouveliotou et al (2013), Wang et al (2013), Beniamini et al (2015), and Fraija et al (2020) have shown that GRBs detected by LAT can be self-consistently modeled using radio, optical, X-ray, and sub-GeV LAT observations self-consistently within the ES model. Kumar & Barniol Duran (2010) interpreted the observed delay of the >100 MeV emission as related to the deceleration timescale of the relativistic ejecta.…”
Section: Introductionmentioning
confidence: 99%
“…GRB 090510 and GRB 130427A are two examples (Fraija et al 2016a,b). Recently, Fraija et al (2020) comprehensively studied the GRB flaring feature detected by Fermi-LAT, and the SSC mechanism in the reverse shock regime can be successfully applied to explain the feature. In this paper, we utilize the jitter radiation process in the kinetic turbulence framework to explain the GRB emission in the TeV energy band.…”
Section: Discussionmentioning
confidence: 99%